Exploring e-commerce adoption among rural entrepreneurs in Sabah: Entrepreneurial motives, perceptions, and facilitators - Bibianah Thomas (2023)
Nowadays, almost all aspects of our lives have been transformed through digitalization due to the advancement of technology, including in business. Therefore, it is important for business organizations to shift their operations from traditional to digital-based technology through the usage of e-commerce. Nevertheless, compared to urban entrepreneurs, rural entrepreneurs, especially in Sabah, face major challenges in transforming their businesses. This will have a substantial impact on the rural economy as they are not gaining the advantages provided by the utilization of e-commerce. Previous studies have investigated e-commerce adoption by looking into the factors, barriers, and disadvantages. However, studies exploring how entrepreneurial motives may influence the facilitators of e-commerce adoption remain limited. For that reason, this study aims to meet four research objectives related to e-commerce adoption. The first is to explore the entrepreneurial motives of rural entrepreneurs in Sabah. The second is to explore the perceptions of rural entrepreneurs in Sabah on e-commerce adoption. The third is to explore the facilitators of e-commerce adoption among rural entrepreneurs in Sabah. Finally, this study will seek to understand how the entrepreneurial motives of rural entrepreneurs in Sabah influence their facilitators of e-commerce adoption. In order to address all these research objectives, this study employs an interpretive qualitative method by using semi-structured interviews to gain an in-depth understanding from 25 rural entrepreneurs in Sabah. The results revealed that the rural entrepreneurs were motivated by both push and pull factors. Besides, the rural entrepreneurs highlighted the benefits and challenges they faced while adopting e-commerce. Then, it was proven that the rural entrepreneurs had been facilitated by social expectancy, performance expectancy, effort expectancy, facilitating conditions, and observational learning. Last but not least, it was found that some entrepreneurial motives had influenced the facilitators of e-commerce adoption to some extent. It is hoped that the findings of this study provide useful insights for the relevant stakeholders to ensure inclusivity of all entrepreneurs in the transition into a digital-based economy.